Mood disorder associated with cannabinoid and codeine use: a case - İzci, Filiz; Bozkurt Zincir, Selma; Bilici, Rabia; Semiz, Ümit Başar (Journal of Dependence, 2014)
Addictive substances cause mood disorders, psychotic disorders and behavioral disorders by affecting the Central Nervous System. Cannabis and codeine, a morphine analog, are substances that have addiction potential. Some preparations used to treat common cold may contain codeine as well as acetaminophen and chlorpheniramine. Here we present a case who had been addicted to cannabis for 6 years and later started to abuse high doses of common cold medications containing codeine and started to show symptoms of mood dysorder with psychotic features.
Keywords: codeine; cannabinoid; mood disorder